Late-Onset Pneumothorax and Bullous Disease in Post-COVID-19 Pneumonia with Severe ARDS - Ira Nurrasyidah; Vincentius Adrian Madargerong; Desi Rahmawaty (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Patients with COVID-19 pneumonia may develop bullae that can rupture into spontaneous pneumothorax (SP) during the diagnosis and treatment, which can be a predictor of a poor prognosis. However, late-onset bullous disease and SP after recovering from COVID-19 are unusual.Case: A 48-year-old male presented with sudden shortness of breath accompanied by chest pain. Three weeks earlier, the patient had finished treatment in the COVID-19 isolation room for 20 days with a diagnosis of COVID-19 pneumonia with severe ARDS. Physical examination demonstrates tachypnea, desaturation, decreased vesicular breath sounds, and hyperresonance percussion on the right hemithorax; without rhonchi or wheezing. Chest X-ray and CT scan showed a right pneumothorax with infected subpleural giant bullae in right perihilar, right lung collapse, minimal right-to-left lung herniation and post-covid pulmonary fibrosis. Culture and sensitivity examination of the pleural fluid showed the growth of Providencia stuartile. A chest tube was placed for the management of the pneumothorax. Subsequently, according to the results of culture and antibiotic sensitivity test, the patient was treated using piperacilin/tazobactam and amikacin. The patient showed clinical and radiological improvement following 41 days of treatment and could be managed as an outpatient.Conclusion: Our patient had infected giant bullae and pneumothorax post COVID-19 pneumonia and severe ARDS. The patient did not undergo a bullectomy in consideration of the post-COVID-19 condition and was managed conservatively using adequate chest tube and antibiotics. Patient responded well to therapy, showed clinical improvement and could be discharged.